Investigation on the Effect of UF resin polymerization variable on strength of Uf bonded Hornbeam particleboard - Ahmad Jahan latibari (Regional Information Center for Science and Technology (RICeST), 1996)
In this investigation, the effect of mat moisture content, press temperature and time on polymerization reaction of urea-formaldehyde (UF)  resin and the strength of UF bonded hornbeam particleboard is studied. Variation of three variables is as followed: -mat moisture content; 10, 13 and 16% (Based on oven dry weight of wood) -Press temperature; 150, 170 and 190 ᵒC -Press time; 4, 6, and 8 min. Fore boards were manufactured for each combination of variables. Modulus of rupture (MOR), modulus of elasticity (MOE), Internal bond (IB), water absorption (Wa2 and Wa24) and thickness swelling (Ts2 and Ts24) after 2 and 24 hours immersion in water were determined according to ASTM 1037 standard. All data was analyzed using factorial design. The effect of mat moisture content on MOR was not statically different, but its effect on MOE was statistically different at 5% significance level, and increasing the mat moisture content from 10 to 16% bout MOR & MOE. Highest level of MOE (4262 MPa) corresponds to board pressed at 16% mat moisture content. On the contrary, mat moisture content decreased the IB and lowest value of IB ( 1.447 MPa) corresponds to boards pressed at 16% mat moisture content. The effect of mat moisture content on IB was statistically different at 1% significance level. Increasing mat moisture content decreased water absorption and increased thickness swelling. Lowest Wa2 & Wa24 was observed on boards pressed at 16% mat moisture content (67.35% & 86.78% respectively) and lowest Ts2 & Ts24 was observed on boards pressed at 10% mat moisture content (21.89% & 27.32% respectively). There force for the production of suitable boards, ma moisture content must be kept at 10-13% range.